Antioxidant Properties of Albizia lebbeck Seed Protein Hydrolysates - Oluwafemi Ekun (International Journal of Applied Biology, 2022)
Peptide based antioxidants from plant and animal proteins are being identified as food additives and also as potential alternatives in the reduction of oxidative stress. This study investigated the antioxidative potentials of peptide digests of Albizia lebbeck seed protein. The proteins were extracted and isolated from A. lebbeck by defatting with n-hexane, followed by alkaline solubilization and acid precipitation of the seed meal. The protein isolate was then subjected to enzymatic hydrolysis using four proteases – pepsin, trypsin, papain and chymotrypsin. The resulting hydrolysates were then evaluated for their abilities to reduce ferric ions, as well as their effects on hydroxyl radicals, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and superoxide radicals. Hydrolysates obtained from peptic proteolysis demonstrated the best activities against DPPH radical and ferric ions (57.589 ± 1.286% and 52.000 ± 0.589 mM Fe2+ respectively), whereas chymotrypsin hydrolysates scavenged superoxide radicals and hydroxyl radicals better than other protein digests (74.520 ± 0.998% and 36.925 ± 1.880% respectively). The choice of enzyme used and the presence of specific amino acid residues at certain positions of peptides in the hydrolysates influenced their antioxidant capacities. It is concluded that Albizia lebbeck seed proteins encode potentially bioactive peptides, which could be harnessed for numerous therapeutic and nutraceutical benefits.